Dual function hydrate inhibitor for prevention of hydrate in methane and carbon dioxide system - Kassim, Z. (Society of Petroleum Engineers, 2019)
Dual function hydrate inhibitor (DFI) is envisaged to provide superior inhibition performances for controlling hydrate formation in comparison to conventional thermodynamic (THI) and kinetic hydrate (KHI) inhibitors. In this work, the performance of DFI was evaluated in high pressure Sapphire cell for methane (CH4) and carbon dioxide (CO2) system. The effects of DFI to the hydrate phase equilibrium conditions at various concentrations for both CH4 and CO2 system were measured in a pressure range of 3.90 â 8.30 MPa and 1.9 â 4.5 MPa respectively. The DFI is then being evaluated for KHI for CH4 and CO2 at 80 bar and 3.5 bar respectively at 274 K experimental temperature. Furthermore, the analysis of induction time and relative inhibition performance are presented for CH4 and CO2 in the absence and presence of DFI. The DFI inhibition performance is strongly evidence as it is observed able to shift hydrate equilibrium conditions, while at the same time prolong the hydrate induction time. In addition, hydrate dissociation enthalpies are also calculated for both considered systems and it was found the enthalpies are within the range of conventional hydrate formation, therefore it is evidence that DFI is not involved during the hydrate cages formation. DFI ability to simultaneously act as THI and KHI shows that DFI performance is more superior as compared to the conventional THI. Copyright 2019, Society of Petroleum Engineers.